Gender differences in elite athletes heart rate dynamics following a supra maximal complex effort - Blasco-Lafarga, C.; Martinez Navarro, I.; March, M. M.; Roldan, A.; Cordellat, A.; Monteagudo, P. (MOJ Sports Medicine, 2017)
Regarding the importance of recovery in sport performance, assessment of post-exercise Heart Rate (HR) Dynamics has become a useful tool to understand such an individual process. Heart Rate Variability (HRV) analysis is widely used as a non-invasive marker of Autonomic Nervous System regulation of HR, where the nonlinear methods (Detrended Fluctuation Analysis (DFA)) have become a promising complementary analysis technique. In order to deepen on the effects of supra maximal complex efforts, integrating specific endurance and strength requirements on cardiac autonomic regulation, our research group is working in different protocols looking for the analysis of specific responses under supra maximal exertion. Therefore, our purpose was to analyze the immediate 10 min recovery timeline following a supra maximal specific Judo test in twenty-four judokas from the Spanish National Team (16 males and 8 females, 24.40 ± 0.97 years), deepening on gender differences. Consistent with previous research on supra maximal protocols, both HRV indices and Short-Term Scaling Exponent (a1), stemmed from DFA, appeared severely depressed after the test. Moreover, a negative correlation was found between final isometric pull-up drill and both lnTP (r=-0.457; p<0.05) and lnLF (r=-0.496; p<0.05), thus suggesting a crucial role for isometric strength requirements in cardiac autonomic recovery after exercise. At the same time, while performance showed a large gender difference (p<0.05; d=0.90), no significant gender differences were found either in HRV indices or in a1. However, when analyzing distance scores to optimal value of a1=1 (|1- a1|), men displayed significantly greater results, thus implying an improved recovery ability. Eventually, our results corroborate that nonlinear methods, compared to linear HRV indices, are capable of detecting subtler changes in HR behaviour.